Modulation of M1/M2 polarization by capsaicin contributes to the survival of dopaminergic neurons in the lipopolysaccharide-lesioned substantia nigra in vivo - Eugene Bok; Young Cheul Chung; Ki‐Suk Kim; Hyung Hwan Baik; Won-Ho Shin; Byung Kwan Jin (2018)
Abstract The present study examined the neuroprotective effects of capsaicin (CAP) and explored their underlying mechanisms in a lipopolysaccharide (LPS)-lesioned inflammatory rat model of Parkinson’s dieases (PD). LPS was unilaterally injected into the substantia nigra (SN) in the absence or presence of CAP or capsazepine (CZP, a TRPV1 antagonist). The SN tissues were prepared for immunohistochemical staining, reverse transcriptase-polymerase chain reaction (RT-PCR) analysis, western blot analysis, blood–brain barrier (BBB) permeability evaluation, and reactive oxygen species (ROS) detection. We found that CAP prevented the degeneration of nigral dopamine neurons in a dose-dependent manner and inhibited the expression of proinflammatory mediators in the LPS-lesioned SN. CAP shifted the proinflammatory M1 microglia/macrophage population to an anti-inflammatory M2 state as demonstrated by decreased expression of M1 markers (i.e., inducible nitric oxide synthase; iNOS and interleukin-6) and elevated expression of M2 markers (i.e., arginase 1 and CD206) in the SN. RT-PCR, western blotting, and immunohistochemical analysis demonstrated decreased iNOS expression and increased arginase 1 expression in the CAP-treated LPS-lesioned SN. Peroxynitrate production, reactive oxygen species levels and oxidative damage were reduced in the CAP-treated LPS-lesioned SN. The beneficial effects of CAP were blocked by CZP, indicating TRPV1 involvement. The present data indicate that CAP regulated the M1 and M2 activation states of microglia/macrophage in the LPS-lesioned SN, which resulted in the survival of dopamine neurons. It is therefore likely that TRPV1 activation by CAP has therapeutic potential for treating neurodegenerative diseases, that are associated with neuroinflammation and oxidative stress, such as PD.